External cephalic version at 38 weeks' gestation at a specialized German single center. - Ann-Sophie Zielbauer (Public Library of Science (PLoS), 2021)
Introduction Cesarean section (CS) rates are increasing worldwide. One constant indication is the breech presentation at term. By offering external cephalic version (ECV) and vaginal breech delivery CS rates can be further reduced. Objective This study aimed to analyze the ECV at 38 weeks of gestation with the associate uptake rate, predicting factors, success rate, and complications at a tertiary healthcare provider in Germany specializing in vaginal breech delivery. Methods We conducted a prospective cohort study with retrospective data acquisition. All women with a singleton fetus in breech presentation presenting after 34 weeks of gestation for counseling between 2013 and 2017 were included. ECV impact factors were analyzed using logistic regression. Results A total of 1,598 women presented for breech birth planning. ECV was performed on 353 patients. The overall success rate was 22.4%. A later week of gestation (odds ratio [OR] 1.69), an abundant amniotic fluid index (AFI score) (OR 5.74), fundal (OR 3.78) and anterior (OR 0.39) placental location, and an oblique lie (OR 9.08) were significantly associated with successful ECV in our population. No major complications were observed. The overall vaginal delivery rates could be increased to approximately 14% with ECV. Conclusion The demand for alternative birth modes other than CS for breech birth is high in the area of Frankfurt, Germany. Our study offers evidence of the safety of ECV at 38 weeks. Centers with expertise in vaginal breech delivery and ECV can reduce CS-rates. To further establish vaginal breech delivery and ECV as alternate options, the required knowledge and skill should be implemented in the revised curricula.